PERBANDINGAN KUALITAS LABA PERUSAHAAN ANTARA PENERAPAN STANDAR AKUNTANSI DOMESTIK DENGAN STANDAR AKUNTANSI INTERNASIONAL - Ani Sri Murwani Kumara Kapti (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2018)
International Accounting Standard have purpose for increasing comparability of financial statement in the world. International Accounting standard also expected have ability to increasing accounting information quality that announce from company. This research examine the changes of earnings information quality between domestics accounting standard and International accounting standard. The changes of earnings quality determine with using ERC (Earning Response Coefficient). ERC that used in this research is ERC with Return Model. The coefficient in regression model that used to calculate ERC with domestic accounting standard compared with international accounting standard. That way used to evaluate usefulness International accounting standard.Based on gathering data in banking companies, we have 18 companies that used in this research. We have result that R Squared (coefficient determination) increase on the company after implemented international standard. R Squared that result from using international standard (0,037) higher than R Squared that result from using Domestic standard (0,020). That means the result show that under international standard the response of announcement of earnings more highly to increasing the capital gain. Unfornutelly, the regression coefficient decrease under international standard from 2.502 to 1.702 but the level of significancy increase, but still insignificant.    Keywords:  Accounting Standard Domestic, Accounting International Standard,Earnings Quality, ERC, Coefficient in Rregression Model, Banking Companies.